Analisis Kapabilitas Aparat Pengawasan Intern Pemerintah Kabupaten Magelang - Nita Safitri (Master in Accounting Program, 2017)
SPIP or Government Internal Control System is an integral processes on every action and activity which done continuously by managers and personnels to give adequate assurance of organization goals achievements. SPIP achievements depends on APIP or Government Internal Supervision Agency’s effectivity. One of many methods to create an effective APIP is by constructing general pattern of capability development which adopted from Internal Audit Capability Model (IACM). IACM consist of internal audit’s fundamental aspects which describes steps to achieve evolutionary five levels on six core internal audit elements.On 2015 Internal Supervision Coordinasion Conference The President of Indonesia entrusted that 85% of APIP will have achieve level 3 in 2019. BPKP representative in Special Region of Yogyakarta 2016 third terms results on monitoring capability of it’s 12 local governments partner for shows that APIP Kabupaten Magelang capability comes last. APIP Kabupaten Magelang overall capability only meet level 1 because 5 elements are stil on level 1. This research was constructed to analyze causal factors of APIP Kabupaten Magelang capability outpaced.This research was conducted by qualitative paradigm, case-study approach and benchmarking method with APIP Kabupaten Bantul and APIP Kabupaten Gunung Kidul. There were two kind of analysis steps: capability reports benchmarking to find APIP Kabupaten Magelang weaknesses, continued with interview trancsriotions analysis to find the causal factors. This research found six causal factors for outpaced APIP Kabupaten Magelang Capability spesifically: audit quantity, administration, IACM comprehension, risk-based planning, non-audit budget, and motivation.